2012
DOI: 10.1063/1.4771686
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of templated-confined nanoscale Au films by thermal-induced dewetting process of a poly(methylmethacrylate) underlying layer

Abstract: In this work, we propose a new approach to prepare surface micro-patterns in nanoscale deposited Au films. In particular, we exploit the idea to use a template confined dewetting aging not directly on the deposited Au film but on an underlying poly(methylmethacrylate) (PMMA) substrate by thermal processes. The idea consists of the following basic concepts: (a) to perform nanoscale Au film deposition assisted by micrometric templates to obtain a template confined film and (b) by low-temperature thermal processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…It is known that metallic nanoparticles and submicron structures over a large area can be prepared via the dewetting of a thin solid metal film on a poorly wetting flat substrate. , Ruffino et al reported the formation of Au nanostructures via the dewetting of Au nanofilms on PMMA substrates. Considering the potential applications of surface structures on PMMA substrates in the patterning of metal films for plasmonics and flexible electronics, the temporal evolution of the pillars formed on PMMA [poly­(methyl methacrylate)] films between two parallel plates under the action of an electric field is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that metallic nanoparticles and submicron structures over a large area can be prepared via the dewetting of a thin solid metal film on a poorly wetting flat substrate. , Ruffino et al reported the formation of Au nanostructures via the dewetting of Au nanofilms on PMMA substrates. Considering the potential applications of surface structures on PMMA substrates in the patterning of metal films for plasmonics and flexible electronics, the temporal evolution of the pillars formed on PMMA [poly­(methyl methacrylate)] films between two parallel plates under the action of an electric field is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. For example, metal nanoparticles (NPs), such as Au and Ag, on conductive transparent substrates show interesting optical properties exhibiting structure-dependent transmission/absorption spectra due to localized surface plasmon resonances [8][9][10][11][12]. On the other hand, for example, Pd and Pt NPs on functional substrates, are particularly interesting due to their catalytic activity in several important chemical reactions on surfaces [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Using thermal-induced dewetting of Au nanolms on poly(methyl methacrylate) underlying layers, Ruffino et al 25 constructed Au nanostructures on PMMA lms. Considering the progress in exible electronics and the potential applications of metallic surface structures on polymer substrates in automobile and aerospace, the eld-induced formation and growth of pillars on BPAPC (bisphenol-A-polycarbonate) lms between two parallel plates is investigated.…”
Section: Introductionmentioning
confidence: 99%